STRATEGI PERTAMINA DALAM MEMENUHI KEBUTUHAN ASPAL DOMESTIK MELALUI PENINGKATAN PANGSA PASAR ASPAL - Achmad Wirawandha Pratama; Tatan Sukwika; Kholil Kholil (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
The purpose of this study is to analyze internal factors (strengths and weaknesses) and external factors (opportunities and threats) as well as alternative strategies for Pertamina to increase the market share of its asphalt products in the business of Pertamina to meet domestic asphalt needs. The design of this research is a case study design the informants of this research are the management of Pertamina and the analysis tools are the SWOT and QSPM methods. The priority business strategy priority strategy of Pertamina to increase the market share of its asphalt products in meeting domestic asphalt needs is the development of distribution networks. Strengths and weaknesses of Pertamina asphalt products are Pertamina has its own factory, has a wide product variance other than asphalt, cooperation with strong agents, synergy with other SOEs, has TKDN, Pertamina brand is considered weaker than foreign brands, competitors have asphalt terminals in the province, lack of supply points in Java and zero term payments. Opportunities and threats that exist are growing private development projects, construction of toll roads, asphalt raw materials other than oil, asphalt substitution products and low barriers to entry for the asphalt business. Pertamina needs to invest, especially in terms of providing facilities and infrastructure for asphalt distribution needs in an effort to meet asphalt demand in areas that are not reached by Pertamina asphalt terminals such as by collaborating on tankers in transporting asphalt to the region.